Metabolomic profiling of the different processes of lambanog production, a traditional Philippine alcoholic beverage - Tabago, Maria Krizel Anne G. (Animo Repository, 2023)
This paper is a preliminary investigation into the various metabolites that may be found in lambanog, a traditional Filipino coconut wine, and looks into the production and manufacturing process that would benefit the local lambanog manufacturers and their community. Using 1H NMR spectroscopy and LC–MS coupled with multivariate statistical analysis and preliminary qualitative analysis using GC–MS, metabolites were tentatively identified from the different processes of lambanog production. Notably, a potential antioxidant is present (chlorogenic acid), especially in the sap and ferment stages. The tentative metabolites found in LC–MS are succinic acid, chlorogenic acid, L-hydroxyglutaric acid, and raffinose. 1H NMR spectroscopy has revealed the presence of ethanol, pyruvate, uracil, and sugars such as glycerol, fructose, mannitol, and glucose. GC–MS studies revealed potential compounds that may influence the organoleptic properties in the stages of lambanog production. In conclusion, the study has shown the potential of analytical tools (LC–MS, 1H NMR Spectroscopy, and GC–MS) in identifying potential metabolites in different stages of lambanog production. Identifying these tentative compounds could enable the development of safer and quality traditional alcoholic beverages, an underutilized field of study in the country. The present study finds application in exploring its quality for public health and commercialization. Keywords: Lambanog, Alcoholic Beverage, Metabolomics, Antioxidant, VOCs, LC–MS, NMR, GC–MS